2003
DOI: 10.1097/01.inf.0000055063.40314.da
|View full text |Cite
|
Sign up to set email alerts
|

Differences in nasopharyngeal bacterial flora in children with nonsevere recurrent acute otitis media and chronic otitis media with effusion: implications for management

Abstract: There are substantial differences in nasopharyngeal flora between children with nonsevere rAOM and children with cOME. The results of nasopharyngeal cultures should be taken into account to avoid treatment with drugs that are ineffective and likely to select resistant organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 28 publications
5
40
4
Order By: Relevance
“…Marchisio et al [26] showed that microbial colonization of the nasopharynx and their resistance patterns are different in patients with OME compared to non-OME cases, which is in contrast to our findings. This difference may be due to geographical varieties or their different antibiotic therapy policy.…”
Section: Resultscontrasting
confidence: 84%
“…Marchisio et al [26] showed that microbial colonization of the nasopharynx and their resistance patterns are different in patients with OME compared to non-OME cases, which is in contrast to our findings. This difference may be due to geographical varieties or their different antibiotic therapy policy.…”
Section: Resultscontrasting
confidence: 84%
“…(iv) The majority of sequences could be classified only at the genus level. Increased numbers of alpha-hemolytic streptococci have been isolated from the nasopharynx of healthy children compared to those for OM-prone children (43,59). We could not achieve specieslevel identification of alpha-hemolytic streptococci using shortread 16S rRNA pyrosequencing technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The association with bronchopulmonary infections occurs because AOM and most lower respiratory tract infections (LRTI) are alternate (or common) outcomes of nasopharyngeal colonization by the same species of respiratory pathogens. Because mortality due to LRTI (Schluger 2010) is more prevalent than that due to intracranial spread of middle ear infection (Monasta et al 2012, WHO 2004 First the pathogens causing rAOM are the same as those causing AOM (Pichichero 2000), but children prone to rAOM experience nasopharyngeal bacterial colonisation more frequently (Faden et al 1991, Harabuchi et al 1994 and with higher density (Stenfors & Raisanen 1992), although this may also be found in children with COME (Marchisio et al 2003)). Quantitative or qualitative defects in plasma immunoglobulins have been found in some, but not all, of those with rAOM (Freijd et al 1984, Freijd et al 1985, Harsten et al 1989, Hotomi et al 1999, Prellner et al 1984b, Stenfors & Raisanen 1993, Yamanaka & Faden 1993.…”
Section: Susceptibility To Raommentioning
confidence: 91%